2019
DOI: 10.1016/j.ijmultiphaseflow.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of airflow above waves in a horizontal pipe

Abstract: We investigate the effect of waves on the airflow in horizontal two-phase pipe flow. Velocity fields in the gaseous phase were acquired by particle image velocimetry (PIV), while interfacial elevation was measured with conductance wave probes. The velocity fields were sampled on a wave-following coordinate system which allows for a decomposition of the velocity field into a mean, wave-coherent and fluctuating component by means of a three-component Reynolds decomposition. Additionally, coherent vortical struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…Previous analysis of the experimental set-up considered in this work (Vollestad et al. 2019 a ) has shown that intermittent airflow separation is a frequent event as the gas flow rate in increased into the amplitude saturation regime described by Ayati et al. (2015), and microscale wave breaking has been observed when the superficial gas velocity , for a superficial liquid velocity (Vollestad et al.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Previous analysis of the experimental set-up considered in this work (Vollestad et al. 2019 a ) has shown that intermittent airflow separation is a frequent event as the gas flow rate in increased into the amplitude saturation regime described by Ayati et al. (2015), and microscale wave breaking has been observed when the superficial gas velocity , for a superficial liquid velocity (Vollestad et al.…”
Section: Introductionmentioning
confidence: 78%
“…(2019 b ) to evaluate phase-averaged statistics of the liquid phase of microscale breaking waves, while the wave-following coordinate system in the gas phase is similar to the coordinate system used by Vollestad et al. (2019 a ), analysing airflow over waves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, PIV has been applied to study the stratified regime in two-phase pipe flow [28][29][30][31][32] . The main results from these studies are spatio-temporally and phase-averaged flow fields.…”
Section: Introductionmentioning
confidence: 99%